Transepidermal water loss in psoriasis: A case-control study - Vrushali N Nikam; Rochelle C Monteiro; Sukumar Dandakeri; Ramesh M Bhat (Wolters Kluwer Medknow Publications, 2019)
Context: Psoriasis is a common papulosquamous disorder characterized by increased epidermal turnover resulting in excessive skin shedding and a compromised barrier function of the skin. Transepidermal water loss (TEWL) is an effective and non-invasive way to measure the barrier function in this condition. Aims: To measure the physiological changes in the skin barrier function in psoriasis by measuring the extent of TEWL. To study the differences in TEWL in pathologically involved and uninvolved skin in psoriasis. To compare the TEWL in skin lesions in psoriatic patients and site matched controls. Subjects and Methods: To determine the barrier quality of the stratum corneum, we performed TEWL measurements using the closed chamber evaporation method (VapoMeter Delfin Technologies, Kuopio, Finland). The ambient temperature ranged between 21°C and 24°C, with a mean relative humidity range of 39%-50%. In total, four sites were measured for all the 50 cases, two involved plaques on the body were selected for the study of lesional psoriatic skin, and the standard sites of ankle and elbow were measured irrespective of being involved or uninvolved with psoriatic skin. TEWL measurements in controls were site matched. Statistical testing was done using SPSS ver. 17. The interval scale data were tested for normality using Shapiro-Wilk test, and between groups testing was done using Mann-Whitney test. Results: The TEWL was higher among the cases in all the four measured areas compared to the controls, thus showing overall impaired skin barrier function in psoriatic skin. In addition, among the cases, the involved sites show higher TEWL in comparison to the uninvolved skin. This is highly suggestive that plaques of psoriasis have reduced water holding capacity. Conclusions: Psoriasis is a dermatosis with overall compromise of the skin barrier function exhibiting exponential TEWL in lesional skin, with increased TEWL over non-lesional skin as well. Thus, it may be concluded that TEWL is an effective, non-invasive and objective method in assessment of skin barrier function.